ANALISIS KEPEMIMPINAN DEMOKASI KEPALA DESA SENDAUR KECAMATAN RANGSANG PESISIR KABUPATEN KEPULAUAN MERANTI - Khusairi, Muhammad; ", Ernawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Democratic leadership of the village head is the ability of a village head in performing duties and responsibilities as a leader in democracy to achieve the goal of government organizations in the village. The purpose of this study is first, to find out how the democratic leadership of the Village Head Sendaur Districts Rangsang Pesisir District Kepulauan Meranti. Second, ie what factors inhibiting the Leadership of the Head of the Village Sendaur Districts Rangsang Pesisir District Kepulauan Meranti.In this study, using the theory put forward by the leadership Vaithzal Rivai (2008:57) give some indicators that is active and dynamic, take decisions by consensus, recevie suggestions from subordinates opinion, and communicative. The study site is located in the village sendaur districts rangsang pesisir district kepulauan meranti. Wherw the informants of this research that village head/secretary of the village, chairman BPD/members BPD, village government officials, village official staff, and villagers Sendaur. This study includes qualitative research into.Results of this study concluded that, leadership village chief in the village Sendaur districts Rangsang Pesisir district Kepulauan Meranti it turned our to be in the unfavorabel category, due to the implementation of democratic leadership is not running optimally. This is due to the village head is less open in conveying information and the implementation of which is less than the maximum meeting. Other than that, distrust, adn the lack of participation of rural communities.Keywords: Leadership, Democracy, Village Head